Teacher Training Effectiveness in Self-Regulation in Virtual Environments - Sáiz-Manzanares, María Consuelo; Almeida, Leandro S.; Martín-Antón, Luis J.; Carbonero, Miguel A.; Valdivieso-Burón, Juan A. (Frontiers in Psychology, 2022)
Higher education in the 21st century faces the challenge of changing the way in which knowledge is conveyed and how teachers and students interact in the teaching-learning process. The current pandemic caused by SARS-CoV-2 has hastened the need to face up to this challenge and has furthered the need to approach the issue from the perspective of digitalisation. To achieve this, it is necessary to design training programmes geared towards teaching staff and which address both the use of technology as well as instructional design aimed at promoting the development of self-regulated learning (SRL) and automatic feedback systems. In this study, work was carried out with 23 teachers (eight inexperienced and 15 experienced teachers) in a training programme conducted through Moodle. The aims were: 1) to test whether there were any significant differences between the behaviour patterns of new teachers compared to experienced teachers, 2) to determine whether clusters of behaviour patterns corresponded to the type of teacher, 3) to ascertain whether the level of teacher satisfaction with the training activity in digital teaching will depend on the type of teacher. A quantitative as well as a qualitative design was applied. Differences were found in the behaviour patterns in the training activities for the development of rubrics and use of learning analytics systems in virtual learning environments. It was also found that the type of teacher did not correspond exactly to the behaviour cluster in the learning platform. In addition, no significant differences were found in the level of satisfaction between the two kinds of teacher. The main contribution this study makes is to provide a detailed description of the training stage as well as the materials required for its repetition. Further analytical studies are required on teacher perception of training programmes in digital teaching in order to provide personalised training proposals that lead to effective teaching in digital environments.